FUNGSI PINJAMAN DARI BAHASA INGGRIS DALAM TEKS BERBAHASA INDONESIA PADA RANAH OLAHRAGA - Ari Nurweni (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
Borrowing of different linguistic units can be encountered in almost all Indonesian texts of various domains, including sport domains. This study aims at describing the functions of borrowing from English in Indonesian texts of sport domains. The data of linguistic units borrowed from English, both loanwords and metaphorical code-switches, in Indonesian texts of sport domains were taken from the sport articles of an Indonesian national newspaper in 2010—2011, and from three sport books, each concerns with techniques of playing sports, sport education, and sport for health. The linguistic units borrowed were analyzed their pragmatic functions based on their external factors, namely, their speech components. The research results show that the linguistic units borrowed from English hold all kinds of pragmatic functions proposed by Jakobson (1973: 54—57) in the texts of sport written in Indonesian. The results imply that even though the functions expressed in the linguistic units borrowed from English are based on some reasons, not all of the functions need to be expressed in those borrowed linguistic units.